2019
DOI: 10.1007/s13402-019-00472-w
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin CD81 mediates the growth and metastases of human osteosarcoma

Abstract: Purpose CD81 is a member of the tetraspanin family of membrane proteins. Recently, it has been shown that CD81 may be involved in cancer cell proliferation and metastasis. As yet, however, there have been few reports on the expression and role of CD81 in osteosarcoma. Methods The expression of CD81 was investigated in human osteoblast cell line hFOB1.19 and in human osteosarcoma cell lines Saos2, MG63 and 143B. The expression of CD81 was inhibited in osteosarcoma cells using siRNA after which cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Human OS cell lines (U2OS, HOS, MG-63) and human embryo immortalized osteoblast hFOB1.19 cells were obtained from the American Type Culture Collection (Manassas, VA, USA) [17,18]. The frozen cells were removed and immediately placed in a thermostatic water bath held at a constant temperature of 37 °C.…”
Section: Cell Culture and Groupingmentioning
confidence: 99%
“…Human OS cell lines (U2OS, HOS, MG-63) and human embryo immortalized osteoblast hFOB1.19 cells were obtained from the American Type Culture Collection (Manassas, VA, USA) [17,18]. The frozen cells were removed and immediately placed in a thermostatic water bath held at a constant temperature of 37 °C.…”
Section: Cell Culture and Groupingmentioning
confidence: 99%
“…2A ), it was found that the migration and invasion of MG63 cells significantly increased following overexpression of lncRNA PCAT6 compared with the NC group. Increased levels of MMP-2 and MMP-9 were closely correlated with metastases of osteosarcoma ( 23 , 24 ). Subsequently, MMP-2 and MMP-9 expression was detected via western blotting.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, although Tumor.C2 appeared relatively “resting” and low risk, it might still promote tumor malignance through up‐regulating a series of worse prognostic genes, such as CD81 , 30 TIMP1 , 31 LGALS3BP , 32 CD151 , 33 etc, suggesting their “standby” status for transforming into Tumor.C2 cells.…”
Section: Resultsmentioning
confidence: 99%